Personalised E-Learning: The assessment of students' prior knowledge in Higher Education - O'DONNELL, EILEEN; SHARP, MARY; WADE, VINCENT (IGI Global, 2014)
Society’s use of mobile applications that instantaneously dynamically adapt to input has had the effect of users expecting immediate feedback from all applications based on their specific needs. The traditional concept of a one size fits all approach to managing an online learning environment could perhaps be improved by the inclusion of personalised learning experiences for students based on their prior knowledge. The purpose of personalised e-learning is to tailor learning content to the specific learning requirements of individual students. The focus of this chapter is to review the topic of personalised e-learning and discuss the issues and problems educators may encounter in assessing students’ prior knowledge. Information on students’ prior knowledge is required to inform the process to facilitate personalised e-learning experiences based on prior knowledge
Handbook of Research on Education and Technology in a Changing Society (2 Volumes)
PUBLISHED
Keywords: e-learning; Creative Technologies; Intelligent Content & Communications